Pengaruh Indeks Prestasi Kumulatif, Stres, dan Motivasi Terhadap Produktivitas Mahasiswa dalam Menyusun Tugas Akhir (Studi Kasus Mahasiswa UNU Kalbar Angkatan 2021) - Pradika, Sidik; Firayanti, Yuni; Marhamah, Marhamah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the influence of Cumulative Grade Point Average (CGPA), stress, and motivation on students’ productivity in completing their final thesis (a case study of Universitas Nahdlatul Ulama Kalimantan Barat students, class of 2021). The background of this research is based on the phenomenon of delays in thesis completion experienced by some students, both those with high and low CGPA, which is suspected to be influenced by stress levels and learning motivation. This study employs a quantitative approach with a survey method through the distribution of questionnaires to 84 respondents selected using a simple random sampling technique. Data were analyzed using multiple linear regression tests with the help of SPSS version 20. The results show that simultaneously, CGPA, stress, and motivation significantly affect students’ productivity with a significance value of 0.000. Partially, CGPA (X1) has a positive effect with a significance value of 0.002, stress (X2) has a negative effect with a significance value of 0.009, and motivation (X3) has a positive effect with a significance value of 0.000. The regression equation obtained is Y = 11.227 + 0.118 – 0.110 + 0.274, with an R² value of 0.445. These findings emphasize the importance of managing academic and psychological aspects of students, particularly in reducing stress and enhancing motivation, to support productivity in thesis completion.